The interplay between extrinsic and intrinsic controls in determining floodplain wetland characteristics in the South African drylands. Issue 7 (14th December 2016) - Larkin, Zacchary T.; Ralph, Timothy J.; Tooth, Stephen; McCarthy, Terence S.
Abstract: Controls on the characteristics of floodplain wetlands in drylands are diverse and may include extrinsic factors such as tectonic activity, lithology and climate, and intrinsic thresholds of channel change. Correct analysis of the interplay between these controls is important for assessing possible channel–floodplain responses to changing environmental conditions. Using analysis of aerial imagery, geological maps and field data, this paper investigates floodplain wetland characteristics in the Tshwane and Pienaars catchments, northern South Africa, and combines the findings with previous research to develop a new conceptual model highlighting the influence of variations in aridity on flow, sediment transport, and channel–floodplain morphology. The Tshwane–Pienaars floodplain wetlands have formed in response to a complex interplay between climatic, lithological, and intrinsic controls. In this semi‐arid setting, net aggradation (alluvium >7 m thick) in the wetlands is promoted by marked downstream declines in discharge and stream power that are related to transmission losses and declining downstream gradients. Consideration of the Tshwane–Pienaars wetlands in their broader catchment and regional context highlights the key influence of climate, and demonstrates how floodplain wetland characteristics vary along a subhumid to semi‐arid climatic gradient. Increasing aridity tends to be associated with a reduction in the ability of rivers to maintain through‐going channels and an increase in the propensity for channel breakdown and floodout formation. Understanding the interplay between climate, hydrology and geomorphology may help to anticipate and manage pathways of floodplain wetland development under future drier, more variable climates, both in South African and other drylands. Copyright © 2016 John Wiley & Sons, Ltd.